(untitled) (Scientific journal of the Fergana State University, 2026)
This article is devoted to the analysis of the profound socio-cultural changes taking place in the fine arts of New Uzbekistan and the philosophical and aesthetic impact of the generational shift within this process. The article examines the dialectical relationships between three generations in the realm of fine arts: (traditionalists, the bridge generation, and young innovators). It reveals the essence of paradigmatic shifts in style—from the traditional realistic school to modern, conceptual, and digital art. The primary focus of the analysis is the process of cultural transformation, where the synthesis of national identity (traditions) with global trends (forms of contemporary art) is evaluated from a socio-philosophical perspective.